Cultivares de soja com potencial de produção de sementes de elevada qualidade fisiológica e tolerância ao armazenamento - Cabral Neto, Luciano Dias (2020)
Storage is a step of great relevance for seed production. Temperature, storage period and differences between cultivars are relevant factors that influence seed storage. The objective of this work was to evaluate the storage of seeds of soybean cultivars, stored under different conditions of temperature and storage period. Two experiments were conducted. The first experiment was conducted at the Federal University of Uberlândia, Campus Monte Carmelo-MG, in the agricultural years 2017/18 and 2018/19. Seeds of cultivars BMX DESAFIO RR8473RSF, RK 6813 RR, M 6210 IPRO, NS 7709 IPRO and SYN 15640 IPRO were stored under constant temperatures of 10, 20 and 30 ° C for 0, 50 and 100 days. The following tests were carried out to assess the physiological quality during storage: first germination count (CP), germination (G), germination under water restriction (RH) and accelerated aging (EA). The experimental was Completely Randomized Design (CRD), with a 5x3x3 factorial, with the averages of 2 agricultural years. There were significant differences in storage between the cultivars evaluated. The seeds of the cultivars BMX DESAFIO RR8473RSF, M 6210 IPRO, NS 7709 IPRO show a greater tendency of quality and tolerance to storage and SYN 15640 IPRO and RK 6813 RR the smallest, with greater differentiation between BMX DESAFIO RR8473RSF and SYN 15640 IPRO. The use of constant temperature in the storage environment at 30 ° C and a period of 50 days is suitable for assessing tolerance to the storage of soybean genotypes. The second experiment was conducted in the 2017/18 agricultural year. The same cultivars from the previous test were used stored at a constant temperature of 20 ° C, in the periods of 0, 50 and 100 days after storage, with a 5x3 factorial design. The tests to assess physiological quality were the same as in experiment 1. Analyzes of isoenzymatic profiles evaluating the enzymes alcohol-dehydrogenase (ADH) and catalase (CAT) were also carried out in the seed laboratory of the Federal University of Lavras (UFLA). There was an indication of greater production of seeds with physiological quality combined with storage tolerance in the cultivars BMX DESAFIO RR8473RSF and M 6210 IPRO in relation to SYN 15640 IPRO and RK 6813 RR. The physiological quality and the expressions of the enzymes ADH and CAT decrease with the advance of the storage period. Seeds from cultivars with higher tendency to high physiological quality and tolerance to storage showed higher CAT expressions throughout the period.